The Legal Framework and Enforcement Issues of Religious Holiday Allowances - Bagijo, Himawan Estu; Bramantya, Alfan; Siwu, Sonya Claudia; Esfandiari, Fitria (Legality : Jurnal Ilmiah Hukum, 2026)
This study examines the legal dilemma between workers’ rights to religious holiday allowances and enforcement challenges using a socio-legal approach integrating normative analysis and empirical data. Religious holiday allowances are mandated under Indonesia Government Regulation No. 36 of 2021 to guarantee workers’ wellbeing during religious festivities. However, enforcement remains problematic in East Java, leaving some gaps between legal provisions and implementation. Based on the data issued by East Java manpower and transmigration office, complaints rose from 23 cases (1,734 workers) in 2022 to 51 cases (5,666 workers) in 2023, then dipped to 27 cases (382 workers) in 2024. This figure climbed again to 36 cases (2,685 workers) in 2025. The 2023 spike and 2025 rebound highlight persistent systemic compliance issues within SMEs and the informal sector. Limited inspection resources, informal settlements, and low employer legal awareness continue to hinder enforcement. This study argues for strengthening institutional enforcement, monitoring systems, and legal literacy to improve religious holiday allowance compliance. This article contributes to labour rights enforcement discussions in Indonesia, illustrating tensions between legal ideals and practical realities within the labour system in Indonesia.